Recruitment bottleneck in aphyllous vanilla seedlings facing drought conditions - Botomanga, Alemao (2025)
Seedling survival is strongly dependent on forest environmental conditions, which in Madagascar have been heavily degraded. Rising temperatures and declining rainfall further exacerbate the vulnerability of these ecosystems. We investigated seedling recruitment across ecologically diverse sites to identify the key factors influencing germination and seedling survival in aphyllous Vanilla species. In situ seedling monitoring and in vitro seed germination trials were conducted to assess tolerance to water stress at various developmental stages. Among the 13 study sites, only three showed positive recruitment rates, with two sites exhibiting rates exceeding 50%. Recruitment was influenced by factors such as fruiting success, soil acidity, high silt content, and clay-rich soil composition. After 12 months of monitoring, approximately 85% of seedlings were lost following severe drought conditions. In vitro asymbiotic germination assays revealed two distinct peaks: rapid germination of immature white seeds after four months, followed by delayed germination of mature black seeds eight months later. The assessment of drought tolerance across protocorm developmental stages exposed to a high-concentration gelling agent revealed that advanced-stage protocorms had increased resistance to water stress. However, no developmental stage was capable of surviving a prolonged six-month drought. Due to the absence of seedling recruitment in several locations, aphyllous vanilla recruitment may benefit from assisted propagation through seed cultures and the subsequent reintroduction of young plantlets into natural habitats. Moreover, conservation and restoration programs should incorporate research on developing soil conditions that facilitate vanilla seedling recruitment.